Spezialstreibstoff für den Ausdauersport - Colombani, P.; Wenk, C. (unimagazin die Zeitschrift der Universität Zürich, 1997)
About the necessary nutrition and diet for endurance athletes with special aspects on carbo hydrates. (aus: Zeitschrift der Universität Zürich 4/96, Bulletin der ETH Zürich Nr. 264/Jan. 1997)